2016
DOI: 10.1007/s00251-016-0916-z
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for selection maintaining MHC diversity in a rodent species despite strong density fluctuations

Abstract: Strong spatiotemporal variation in population size often leads to reduced genetic diversity limiting the adaptive potential of individual populations. Key genes of adaptive variation are encoded by the immune genes of the major histocompatibility complex (MHC) playing an essential role in parasite resistance. How MHC variation persists in rodent populations that regularly experience population bottlenecks remains an important topic in evolutionary genetics. We analysed the consequences of strong population flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Genes that compose the major histocompatibility complex (MHC) capture an essential fraction of adaptive genetic variation underpinning resistance to pathogens [15,16] and have proved to be useful in examining the adaptive potential of populations in mammalian species [17][18][19][20]. The high polymorphism of MHC has been demonstrated to be maintained by balancing selection driven by pathogens [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Genes that compose the major histocompatibility complex (MHC) capture an essential fraction of adaptive genetic variation underpinning resistance to pathogens [15,16] and have proved to be useful in examining the adaptive potential of populations in mammalian species [17][18][19][20]. The high polymorphism of MHC has been demonstrated to be maintained by balancing selection driven by pathogens [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been suggested that MiSeq improves our ability to discern true alleles from artefacts in species with many MHC genes [ 25 ], this has yet to be tested directly. This is an important omission as there is still a great deal of research being published that has used 454 for MHC genotyping [ 31 , 35 39 ]. Thus, it is valuable to determine, in species with many MHC gene copies, how 454 and MiSeq genotyping compares.…”
Section: Introductionmentioning
confidence: 99%
“…The active role of selection during bottleneck events has been previously demonstrated in experimental populations of Drosophila melanogaster [45,46]. A few other studies have found recent signatures of selection at MHC loci in natural populations despite the presence of bottleneck events (e.g., [36,37,38,39,40,41]). Our study adds, therefore, to the body of literature suggesting that selection can potentially mitigate the effects of genetic drift during demographic bottlenecks.…”
Section: Discussionmentioning
confidence: 79%
“…Since demographic bottlenecks result in a significant decrease in N e , genetic drift would tend to outweigh the effect of balancing selection on MHC variation [34,35]. While most studies suggest that MHC loci become effectively neutral during population bottlenecks (e.g., [12,25,26,28]), some studies have found that balancing selection can outweigh genetic drift and produce recent signatures of selection [36,37,38,39,40,41]. Thus, there is still considerable debate about the relative roles that natural selection and genetic drift may play in shaping genetic diversity during population bottlenecks [2,42,43,44,45,46].…”
Section: Introductionmentioning
confidence: 99%